2014
DOI: 10.1002/2014wr015320
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ground and airborne geophysical data with upscaling techniques for regional groundwater modeling of heterogeneous aquifers: Case study of a sedimentary aquifer intruded by volcanic dykes in Northern Ireland

Abstract: In highly heterogeneous aquifer systems, conceptualization of regional groundwater flow models frequently results in the generalization or negligence of aquifer heterogeneities, both of which may result in erroneous model outputs. The calculation of equivalence related to hydrogeological parameters and applied to upscaling provides a means of accounting for measurement scale information but at regional scale. In this study, the Permo-Triassic Lagan Valley strategic aquifer in Northern Ireland is observed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 105 publications
2
38
0
5
Order By: Relevance
“…All studies indicated that borehole logs and groundwater level measurements were used to constrain the model. In a recent study by Dickson et al (2014), structural information directly namely the Sherwood Sandstone Group (SSG), which is the country's principal aquifer for industrial use and domestic supply, commonly named the Lagan Valley Aquifer. The SSG is bounded by Silurian rocks outcropping to the south-east and upland Palaeogene chalk and basalt to the north-west.…”
Section: Multiple-point Statistics and Direct Sampling Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…All studies indicated that borehole logs and groundwater level measurements were used to constrain the model. In a recent study by Dickson et al (2014), structural information directly namely the Sherwood Sandstone Group (SSG), which is the country's principal aquifer for industrial use and domestic supply, commonly named the Lagan Valley Aquifer. The SSG is bounded by Silurian rocks outcropping to the south-east and upland Palaeogene chalk and basalt to the north-west.…”
Section: Multiple-point Statistics and Direct Sampling Techniquementioning
confidence: 99%
“…The effect of dykes on groundwater flow is acknowledged by previous authors as acting as relative barriers to flow: the hydraulic effect is described in Bennett (1976), Kalin and Roberts (1997), Burns et al (2010), Wilson (2011) and numerous consultancy studies involving hydraulic testing. Despite those references, few (Wilson 2011;Comte et al 2012;Dickson et al 2014) have actually attempted to quantify both the properties of dykes and their effect at local to regional scales. Prior to the detailed multi-scale modelling works by Dickson et al (2014), modelling studies by Cronin et al (2000), Yang et al (2004) and Cronin et al (2005) mention that dykes were taken into account through compartment zonation of approaches can be used to integrate an exhaustive map of geophysical data in the MPS framework.…”
Section: Multiple-point Statistics and Direct Sampling Techniquementioning
confidence: 99%
See 3 more Smart Citations